Efektivitas Implementasi Kebijakan Dana Desa dalam Mendorong Pembangunan Infrastruktur Berkelanjutan dan Kemandirian Masyarakat di Kampung Datah Bilang Baru - Imiliana Imiliana; Sri Roekminiati; Ika Devy Pramudiana (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to analyze the effectiveness of the Village Fund policy implementation in Datah Bilang Baru Village in fostering sustainable infrastructure development and community independence by employing Edwards III's implementation theory, which encompasses communication, bureaucratic structure, resources, and disposition variables. This study utilizes a descriptive qualitative method with data collection techniques through in-depth interviews, field observations, and documentation studies. The findings indicate that the communication dimension successfully reduced information distortion through the adaptive translation of policy language; the bureaucratic structure operated effectively through the implementation of rigid Standard Operating Procedures with 100% tiered verification that mitigated corruption risks; logistical resource constraints were overcome through local human resource training interventions and independent facility procurement; and implementer disposition demonstrated a high commitment to integrity, ensuring physical infrastructure specifications met SNI standards without compromising material quality. It can be concluded that the Village Fund policy implementation in Datah Bilang Baru Village has proven to be highly effective, where the synergy of the four Edwards III determinants was able to produce sturdy and sustainable farm road infrastructure and stimulate community independence through the cash-for-work system. This study recommends the necessity of institutionalizing the existing participatory communication model and increasing specific budget allocations for technical competency certification for the village's younger generation to ensure the regeneration of professional and accountable development management resources in the future.